Investigation of biometric-based techniques for e-security - Mohamed Mohsin Ismail. (2011)
This report will examine the authentication of identity in the context of the Internet as well as the various computer based applications. By taking a look at the history of online authentication, the various measures to enhance security and the different types of authentication available today, this report will seek to understand and improve on these techniques.